Portable solar panel with Mamdani fuzzy logic controller for sun position tracking and IoT monitoring system - Hanafi, Dirman; Salleh, Ahmad Faris; Rahman, Hisyam Abdul; Zakri, Azriyenni Azhari; Ribuan, Mohamed Najib; Ghazali, Rozaimi (2023)
Nowadays, solar energy from the sun is one of the most useful renewable energy to generate electricity with many advantages that has contributed a lot in discovering new technologies to generate energy supplies for the good uses around the world. Currently, solar panel is installed with a fixed position. This causes the panel to be unable to absorb sunlight energy optimally. Therefore, in this paper a prototype solar panel system is designed which can track the position of the sun. The Mamdani type fuzzy logic controller is applied to ensure the position of the solar panels is always perpendicular to the sunlight. Real Time Clock (RTC) sensors are applied as input variable for controller and to be able to provide the right input signal to the controller, several light sensors are used and installed in an array. Besides that, this system also can be controlled through IoT using Blynk Application and can be accessed through smart phone. Using this mechanism, the solar panel system can acquire energy maximally. Based on real time experimental tested on two weather conditions from 7.00 am to 4.00 pm, namely sunny and during the cloudy, it can be seen that on a sunny day this system can absorb a total energy of 94.7W and cloudy day is 33.3W.